Teaching English in International English Classrooms: Pedagogical Challenges and Opportunities in Linguistically Diverse Classrooms at Muhammadiyah University of North Maluku - Djafar, Hariyanti; Muhamad, Sariwati; Nasir, Vebiyanti; Sahmadan, Safrudin (Edumaspul: Jurnal Pendidikan, 2025)
The internationalization of higher education has reshaped English language classrooms into linguistically and culturally diverse spaces where English functions primarily as a lingua franca rather than a native speaker norm. This transformation presents complex pedagogical challenges as well as meaningful opportunities for English language educators, particularly in contexts characterized by heterogeneous student populations. This study examines the challenges and opportunities encountered in teaching international English classes at Muhammadiyah University Maluku Utara and explores instructional strategies that support inclusive and effective learning. Employing a qualitative research design, data were collected through semi-structured interviews with English instructors, student questionnaires, classroom observations, and document analysis. The data were analyzed using thematic analysis to identify recurring patterns in educators’ experiences and classroom practices. The analysis yielded three major themes: pedagogical challenges in international English classrooms, opportunities in linguistically and culturally diverse classrooms, and adaptive teaching strategies. The results reveal that instructors face persistent challenges related to uneven English proficiency levels, pronunciation and accent variation, cultural differences in classroom interaction, and the complexity of implementing fair assessment practices across diverse educational backgrounds. Despite these challenges, international English classrooms provide substantial opportunities for intercultural learning, collaborative engagement, and the development of global communication skills. Linguistic and cultural diversity was found to enrich classroom interaction, promote critical thinking, and enhance students’ readiness for participation in global academic and professional contexts. Furthermore, the study highlights the effectiveness of interactive, collaborative, and technology enhanced pedagogical approaches in facilitating differentiated instruction and inclusive participation